1992
DOI: 10.1002/ardp.19923251105
|View full text |Cite
|
Sign up to set email alerts
|

Tinocrisposid, ein neues Furanoditerpenglykosid aus Tinospora crispa Miers

Abstract: Aus Stengeln vonAus dem Methanolextrakt der Stengel isolierten wir nach Abtrennung der N-Acylaporphine als neues, Dragendorflpositives Furanoditerpenglykosid Tinocrisposid (l), uber dessen Strukturaufklarung hier berichtet werden soll. Furanoditerpene wurden schon haufiger als bittere Inhaltsstoffe in anderen Menispermaceen, besonders aber in der Gattung Tinospora g e f~n d e n~?~.~) .Aus Tinospora tuberculata Beumee (syn. T. crispa) wurde Borapetosid A beschrieben*), das sich von 1 u.a. durch eine zusatzliche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In this study, we used tinocrisposide as a test compound which was isolated from methylene chloride fractions of T. crispa stems. The isolation process was conducted according to our previous method by Pachaly and Adnan [8]. The structure of the compound was identified spectroscopically and confirmed with previous data in our publication.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In this study, we used tinocrisposide as a test compound which was isolated from methylene chloride fractions of T. crispa stems. The isolation process was conducted according to our previous method by Pachaly and Adnan [8]. The structure of the compound was identified spectroscopically and confirmed with previous data in our publication.…”
Section: Resultssupporting
confidence: 63%
“…From methanol extract of dried pulvered T. crispa stems, we have isolated tinocrisposide (C 27 H 36 O 11 ), a furano diterpene glycoside with very bitter taste. This work has been reported in Arch Pharm [8]. An antiinflammatory effect of tinocrisposide has been investigated in vivo in our previous study and reported in 43 rd GA-Congress in Halle, Germany [9].…”
Section: Introductionmentioning
confidence: 99%
“…(Menispermaceae) popularly known as Amrita in Sanskrit, has been used for several centuries in Ayurvedic medicine for the treatment of various ailments (Chadha, 1976). This species is rich in clerodane derived diterpenes (Pachaly and Adnan, 1992;Rahman et al, 1992;Fukuda et al, 1993;Gangan et al, 1995;Maurya, 1996;Martin et al, 1996). Previously, we reported on the isolation and characterization of several new furanoditerpene glucosides Maurya et al, 1995) from T. cordifolia.…”
Section: Introductionmentioning
confidence: 96%
“…This hypoglycemic effect was likely due to by insulinotropic mechanism [2]. From methanol extract of dried pulverized T. crispa stems, tinocrisposide (C 27 H 36 O 11 ) has been isolated, a furanoditerpene glycoside with a very bitter taste [4]. It is considered that tinocrisposide is responsible for some biological activity of T. crispa stem extracts so that it has been used as an antidiabetic treatment in traditional medicine (Fig.…”
Section: Introductionmentioning
confidence: 99%